EVALUATING GIRLS STUDENTS DORMITORIES WITH AN EMPHASIS ON COMFORT AND INTIMACY - Kameli, Mohsen; Fakhri, Maryam; Mohammadi, Maryam (Ciência e Natura, 2016)
Many researches, performance in the field of social behavior, have evaluated the issue of intimacy along with culture, religion and environment, intimacy is very important in girls dormitory; the issue of intimacy, as a principle dominating all aspects of life, has beautifully been introduced and discussed in Iranian architecture. The factor of being Iranian integrated with Islamic culture, art and thought, as given a new feature to Iranian art. The present research aims to study student dormitories with the emphasis on comfort & intimacy. The research method is descriptive – analytic based on surveys; and the technique is using questionnaire. The statistical population is the students living in the city of Tafresh with 300 samples selected purposefully. According to the results, the variables of comfort and intimacy not only can be useful for the security of girls hostel, it also can affect the relationships of the students with outside the dormitory and their comfort inside the dormitory. Regarding the component of intimacy in designing dormitory, it possible to create maximum spaces inaccessible to others; building unroofed, cozy and open spaces helps students to reside in this place for longer time, and to feel safety in this environment as their own home. Comfort and intimacy are of mutual relations; the more you consider the principles of intimacy, the more the girls of hostel feel comfortable.